EFFECT OF MANGANESE FERTILIZATION ON DRY MATTER YIELD AND MANGANESE AND IRON ABSORPTION BY PEA (PISUM SATiVUM) AT TWO STAGES OF GROWTH - Baser, B L; Saxena, S N (Annals of Arid Zone, 2016)
Effect of soil application of manganese as manganese sulphate on dry matter production and manganese and iron absorption by pea (Pisumm sativum) at two stages of growth was studied. It has been found that on .an average 20 kg/ha application of manganese sulphate increased ,he yield significantly. With increasing application of manganese sulphate manganese concentration increased while iron concentration and iron manganese Â·ratio in plants decreased. The increase and decrease was highly significant when manganese sulphate was applied @ 20 kg/ ha. The almost same iron/manganese ratio at the two stages of growth of plants, indicated that iron and manganese were being utilised in the same proportion throughout the growth of the plants.